The Jesuits, 1534-1921 A History of the Society of Jesus from its Foundation to the Present Time. - Campbell, Thomas J. (Auckland : The Floating Press, 2014)
The largest religious order in the Catholic Church, the Jesuits have played a major role in the religion since the order's founding in 1540. In this comprehensive history from Thomas J. Campbell, the contribution of the Jesuits -- particularly in the realms of scholarly pursuits, theology, and evangelism -- are laid out in a compelling, highly detailed narrative.
Chapter XVII -- The Final BlowChapter XVIII -- The Instrument; Chapter XIX -- The Execution; Chapter XX -- The Sequel to the Suppression; Chapter XXI -- The Russian Contingent; Chapter XXII -- The Rallying; Chapter XXIII -- The Restoration; Chapter XXIV -- The First Congregation; Chapter XXV -- A Century of Disaster; Chapter XXVI -- Modern Missions; Chapter XXVII -- Colleges; Chapter XXVIII -- Literature; Chapter XXIX -- The Sovereign Pontiffs and the Society; Chapter XXX -- Conclusion
Description based upon print version of record.
Keywords: Jesuits -- History; Jesuits; Religion; Jesuits -- History; RELIGION / Comparative Religion; RELIGION / Essays; RELIGION / Reference; Electronic books